Analisis Determinan Keputusan Pembelian: Kualitas Produk, Label Halal, Harga, dan Inovasi dalam Konteks HNI di Ungaran Timur - Iin Suryani (Nur Science Institute, 2024)
This research analyzes the influence of product quality, halal label, price, and product innovation on consumer decisions to purchase HNI products. The data collection method uses a questionnaire where the population is consumers who have used HNI products in the East Ungaran District, Kab. Semarang. By using 50 respondents as samples. This research shows that product quality has a positive and insignificant effect on consumer purchasing decisions for HNI products in the East Ungaran District, Kab. Semarang. Halal labels have a positive and negligible effect on consumer purchasing decisions for HNI products in the East Ungaran District, Kab. Semarang. Price has no positive or significant influence on consumer purchasing decisions for HNI products in the East Ungaran District, Kab. Semarang. Product innovation significantly affects consumer purchasing decisions for HNI products in the East Ungaran District, Kab. Semarang.Keywords: Product Quality, Halal Label, Price, Product Innovation, Purchase Decision.